Implementasi Pencatatan Laporan Akuntansi Pada Usaha Mikro Kecil dan Menengah : (Studi Kasus Usaha Rumahan Rempeyek Kacang di Desa Laden, Pamekasan) - Ismi Millah Tibyana; Yunita Agustini; Eka Damayanti; Aditya Romansyah; Mochamad Reza Adiyanto (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research investigates the application of accounting financial statements in micro-enterprises, specifically focusing on home-based rempeyek businesses in Desa Laden, Pamekasan. Employing qualitative descriptive methods and interviews, the study explores the obstacles and advantages of implementing accounting systems in UMKM. The findings reveal a lack of awareness among business owners regarding financial statements, resulting in underutilization of financial reports for business administration. There is a call for governmental initiatives to provide training and guidance aimed at enhancing UMKM development in Pamekasan.